Introducing intercultural communication global cultures and contexts - Liu, Shuang; Volcic, Zala; Gallois, Cynthia (Sage, 2015)
Introducing Intercultural Communication uses examples and case studies from around the world to situate communication theory in a truly global perspective. Covering the essentials from international conflict to migration and social networking, this book shows students how to master the skills and concepts at work in how we communicate and understand each other across cultural boundaries. Each chapter brings to life the links between theory and practice, and between the global and local, showing you how to understand the influence of your culture on how you view yourself and others. In this book: theory boxes show you how to use key ideas in work contexts; case studies from European, Chinese, Australian and American contexts give you a truly global perspective; critical questions help you to challenge yourself; a full chapter gives practical tips on how to become an effective intercultural communicator; annotated lists of further reading and free access to online SAGE journal articles assist you in your research; and, a companion website provides you with exercise questions, as well as extended reading lists. This book will guide you to success in your studies and will teach you to become a more critical consumer of information.